2000
DOI: 10.1074/jbc.m003755200
|View full text |Cite
|
Sign up to set email alerts
|

TWIK-2, an Inactivating 2P Domain K+ Channel

Abstract: We cloned human and rat TWIK-2 and expressed this novel 2P domain K ؉ channel in transiently transfected COS cells. TWIK-2 is highly expressed in the gastrointestinal tract, the vasculature, and the immune system. Rat TWIK-2 currents are about 15 times larger than human TWIK-2 currents, but both exhibit outward rectification in a physiological K ؉ gradient and mild inward rectification in symmetrical K ؉ conditions. TWIK-2 currents are inactivating at depolarized potentials, and the kinetic of inactivation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
111
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 31 publications
16
111
0
Order By: Relevance
“…The current deviated from that of an ideal background channel as the activity was influenced by the membrane potential. About 50% of TWIK-2 inactivated slowly ( ϳ2 s) at strong depolarization (steady-state half inactivation at ϩ65 mV) (270), while the remaining fraction showed background K ϩ current properties (270). The inactivation was also modified by the extracellular K ϩ concentration.…”
Section: Twik (Tandem Of Pore Domains In a Weak Inward Rectifyingmentioning
confidence: 97%
See 1 more Smart Citation
“…The current deviated from that of an ideal background channel as the activity was influenced by the membrane potential. About 50% of TWIK-2 inactivated slowly ( ϳ2 s) at strong depolarization (steady-state half inactivation at ϩ65 mV) (270), while the remaining fraction showed background K ϩ current properties (270). The inactivation was also modified by the extracellular K ϩ concentration.…”
Section: Twik (Tandem Of Pore Domains In a Weak Inward Rectifyingmentioning
confidence: 97%
“…Coexpression of TWIK-1 and TWIK-2 subunits also failed to induce K ϩ current (279). Interestingly, rat TWIK-2 produced 15-fold higher currents than the human channel in COS-7 cells; thus rat TWIK-2 was more readily characterized (270). According to these (sometimes contradictory) reports, the expression of TWIK-2 may also be limited in the different expression systems (with the possible exception of rat TWIK-2).…”
Section: Twik (Tandem Of Pore Domains In a Weak Inward Rectifyingmentioning
confidence: 99%
“…Previous studies showed that a disulphide bridge is not required for the formation of TWIK-2 (ref. 28) or TASK-2 (ref. 29) homodimers.…”
Section: Discussionmentioning
confidence: 99%
“…They are only moderately inhibited by Ba 2ϩ , the most sensitive being TWIK1 (Kcnk1, K 2P 1.1) and TWIK2 (KCNK6, K 2P 6.1), with Ba 2ϩ concentrations inhibiting 50% of the max currents (IC 50 ) around 100 M (Lesage et al, 1996;Patel et al, 2000). Ba 2ϩ IC 50 for TASK1 and TASK3 are much more important and comprised between 300 M and 3 mM (for review, see Goldstein et al, 2005).…”
Section: ؉mentioning
confidence: 99%